Anti-NMDAR Encephalitis and Myasthenia Gravis Post-COVID-19 Vaccination: Cases of Possible COVID-19 Vaccination-Associated Autoimmunity - Simanungkalit, Astra Dea; Puspitasari, Vivien; Margono, Jacqueline Tasha; Tiffani, Pamela; Stevano, Reza (Open Access Macedonian Journal of Medical Sciences, 2022)
Abstract BACKGROUND: Coronavirus disease 2019 (COVID‐19) continues to be a global issue. While immunizations comprise an important line of defense against it, adverse effects may occur. We report two cases of autoimmune conditions affecting the nervous system, anti-N-Methyl-D-Aspartate-receptor (NMDAR) encephalitis and myasthenia gravis (MG), that developed in close association following COVID-19 vaccination. CASE REPORT: In our first case, a 29-year-old woman presents with recurrent seizures, auditory hallucinations, psychiatric symptoms, and autonomic abnormalities, with an onset of one day after receiving the second dose of inactivated SARS-COV-2 whole virus vaccine. CSF analysis and electroencephalogram (EEG) was consistent with anti-NMDAR encephalitis. In our second case, a 23-year-old woman presents with ocular ptosis, diplopia, hoarseness, and fatigability, which first appeared one-day after her first dose of inactivated SARS-COV-2 whole virus vaccine. Electromyography (EMG) results established a definitive diagnosis of MG. CONCLUSION: To our knowledge, this is the first report of anti-NMDAR encephalitis and MG associated with inactivated SARS-COV-2 whole virus vaccine. In both cases, COVID-19 vaccination appears to be the only remarkable feature of history. The authors postulate that COVID-19 vaccination may trigger underlying defects or induce failure of positive and negative selection, which may lead to autoreactivity and subsequent autoimmunity. However, further studies are required to confirm this possibility.